Gambaran Kadar Karboksihemoglobin (COHb) pada Mahasiswa Pengguna Sepeda Motor - Sinta Nuriyah; Purwati Purwati; Tri Harningsih (Jurnal Farmasetis, 2022)
Carbon monoxide (CO) is a colorless, odorless and tasteless gas. Exposure to high concentrations of carbon monoxide gas during continuous exposure can cause an increase in blood COHb levels. The purpose of this study was to determine the level of carboxyhemoglobin based on the length of exposure in students. The method of examination uses the Conway diffusion cell. The samples used were 7 samples from students at one of the universities in Sukoharjo. The sampling technique uses quota sampling. Data is collected started by charging informan consent as evidence samples probandus agreed in this research. It is filling out the questionnaire and obtained 7 sample qualifies as probandus in this research. Blood sampling on the probandus was carried out on the same day. COHb levels in the samples were examined sequentially as results: 0,43%; 0,41%; 0,32%; 0,34%; 0,47%; 0,48%; and 0,46%. All samples examined had COHb levels below the standard threshold of the PERMENKES RI No. 70 of 2016 which was not more than 3,5%.